Keterampilan Motorik Kasar Dengan Hasil Belajar Pendidikan Jasmani Olah Raga Kesehatan - Sania, Aes; Arsil, Arsil; Asnaldi, *Arie (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The problem in this research is the low gross motor skills of elementary school students 01 Beremas River, Kenagarian Cubadak, Duo Koto District, Pasaman Regency. This study aims to see the relationship between gross motor skills and physical education learning outcomes of students at the State Elementary School 01 Sungai Beremas, Dua Koto District, Pasaman Regency. This type of research is correlational which aims to see the relationship between gross motor skills and physical education learning outcomes. The population of this study were 97 students of state elementary school 01 Sungai Beremas, Duo Koto District, Pasaman Regency, while the sample was taken by purposive sampling in order to obtain a sample of 40 people. Gross motor skills use a basketball throwing test, a 4 second sprint test, a wall ball passing test and a standing board jump test. Data analysis was performed using product moment analysis. Based on the results of data analysis, it shows that; There is a significant relationship between gross motor skills and the learning outcomes of Physical Education for Students in SD Negeri 01 Sungai Beremas, Dua Koto District, Pasaman Regency.